A grab to move on: ER–endosome contacts in membrane protrusion formation and neurite outgrowth - Krauß, Michael (EMBO J, 2015)
A key feature of many eukaryotic cells, most prominently seen in developing neurons, is their ability to form and extend membrane protrusions. How protrusion formation is linked to exocytic membrane trafficking is largely unclear. In a recent paper published in Nature, Raiborg et al identify a crucial role in this process for dynamic membrane contact sites (MCSs) between the ER and endosomes. The MCSs are formed by endoplasmic reticulum (ER)-localized protein protrudin and the late endosomal kinesin adaptor FYCO1 and the small GTPase Rab7.